Blurry Vision as a Presentation of Waldenström's Macroglobulinemia: A Case Report With Review of Current Management - Tyler Nicholas Adams BS; Rachna Jetly-Shridhar MD; Dat Tran MD; Brian C. Boulmay MD (SAGE Publishing, 2022)
A patient was diagnosed with Waldenström's macroglobulinemia (WM) after the initial findings of anemia and ophthalmological findings of retinal hemorrhage. Upon further workup, the patient was found to have an IgM predominant monoclonal gammopathy on serum protein electrophoresis (SPEP) and urine protein electrophoresis (UPEP). This highlights the need for open communication between different specialties, streamlining rapid and accurate diagnosis. Also highlighted are the unique pathophysiological changes involved in the development of WM. A patient's primary complaint was blurry vision. After the patient was noted to have a monoclonal gammopathy on SPEP, bone marrow biopsy was performed. The bone marrow biopsy findings were consistent with lymphoplasmacytic lymphoma (LPL). The patient received plasmapheresis and chemotherapy. The disease course is described. The patient saw rapid improvement in all lab abnormalities after the beginning of the appropriate therapy of plasmapheresis and chemotherapy. Remission is common with WM. Regular follow-up with this patient is important.